School's Out: Experimental Evidence on Limiting Learning Loss Using "Low-Tech" in a Pandemic - Noam Angrist; Peter Bergman; Moitshepi Matsheng (Institute of Labor Economics (IZA), 2020)
Schools closed extensively during the COVID-19 pandemic and occur in other settings, such as teacher strikes and natural disasters. This paper provides some of the first experimental evidence on strategies to minimize learning loss when schools close. We run a randomized trial of low-technology interventions – SMS messages and phone calls – with parents to support their child. The combined treatment cost-effectively improves learning by 0.12 standard deviations. We develop remote assessment innovations, which show robust learning outcomes. Our findings have immediate policy relevance and long-run implications for the role of technology and parents as partial educational substitutes when schooling is disrupted.
Keywords: I2; I24; 330; education; covid; experiment; remote learning; COVID-19